Molecular Docking of Betel Leaf (Piper betle L.) on Protein Dihydrofolate reductase of Mycobacterium tuberculosis - Endriyatno, Nur Cholis (Science and Community Pharmacy Journal, 2022)
Tuberculosis is an infectious disease of global concern. The treatment challenge of tuberculosis is bacterial resistance to antibiotics. Therefore, it is necessary to search for alternative treatments, one of which is the molecular docking method of Phytol, Chavibetol, Hydroxychavicol compounds contained in betel leaves. The target proteins used were 4KL9 and 4KM2 of the Dihydrofolate reductase pathway in Mycobacterium tuberculosis bacteria. Dihydrofolate reductase is a therapeutic target in the development of antituberculosis drugs. The molecular docking results showed that the target protein 4KL9 with Phytol, Chavibetol, and Hydroxychavicol compounds had a lower binding affinity when compared to the native ligand. In the 4KM2 target protein, these three compounds have a higher binding affinity value than the native ligand. This value indicates the strength of the ligand when it binds to the target protein, the smaller the value, the stronger the bond. In addition, there are similar residues involved in the target protein 4KL9 between the native ligand and the test compound, but in the target protein 4KM2 there is no similarity in the residues between the native ligand and the test compound. Residual similarity describes the similarity of the test ligand properties to the native ligand. It can be concluded that Phytol, Chavibetol, Hydroxychavicol compounds contained in betel leaf have potential as antituberculosis in the dihydrofolate reductase pathway on the target protein 4KL9 of Mycobacterium tuberculosis.